A Revisionary Theoretical Framework of Responsibility: A Philosophical Exploration of Incapacity for Responsible Behaviour (utilregnelighet) - Søvik, Atle Ottesen (Bergen Journal of Criminal Law & Criminal Justice, 2019)
The article presents the main features of a theory of responsibility and the conditions that determine who can and cannot be held responsible, with a focus on different types of incapacity for responsible behaviour. The article has four parts. The first three parts answer the following questions: what is responsibility; what is capacity for responsible behaviour; and, what is incapacity for responsible behaviour. Part four answers some possible objections. The answers are based on Antonio Damasio’s understanding of the mind, Manuel Vargas’ revisionary theory of responsibility, and previous work by the author on free will.